Conductive material mixtures and layers for manganese-rich cathode electrodes

By forming a precoat of carbon and carbon nanotubes on the metal current collector of lithium-ion batteries and depositing lithium-rich manganese slurry on it, the problem of increased internal resistance of lithium-rich manganese electrodes in a low charge state is solved, and the internal resistance of the electrode and the improvement of cell performance are achieved.

CN119833543APending Publication Date: 2025-04-15FORD GLOBAL TECH LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411361727.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-05
Filing Date
2024-09-27
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Lithium-rich manganese electrodes may have increased internal resistance in low charge states, affecting the performance and efficiency of the cell.

Method used

Using a layering method, a precoat consisting of carbon, carbon nanotubes and binder is formed on the metal current collector, and a lithium-rich manganese (LMR) slurry is deposited thereon to form a two-layer structure of conductive material to reduce resistance.

Benefits of technology

By increasing the combination of conductive materials, the internal resistance of the electrode is reduced, potentially improving the power capacity and the overall performance of the battery cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833543A_ABST
    Figure CN119833543A_ABST
Patent Text Reader

Abstract

Conductive material mixtures and layers for manganese rich cathode electrodes are provided. A lithium ion battery having an enhanced electrode structure and a method for forming such an electrode structure. An electrode assembly includes a precoat layer compressed with a metal current collector, and then a lithium-rich manganese active layer is deposited on the metal current collector and compressed to form the assembly. The disclosed electrode structure reduces internal resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to electrode materials for lithium-ion batteries. Background Art

[0002] Lithium-ion batteries are widely used in various applications. One of the contributing factors to the performance of lithium-ion batteries is the electrode structure, which plays a role in the energy density, power density and cycle life of the battery. In this context, different cathode materials have been studied to optimize these properties. Manganese-rich cathodes have higher internal resistance compared to high-nickel, nickel-cobalt-manganese battery cell formations. Pre-coated conductive layers on the current collector can reduce the interfacial resistance. Summary of the invention

[0003] In one aspect, the electrode assembly includes: a metal current collector; a coating composed of dispersed carbon, carbon nanotubes, and a binder, the coating being compressed together with the metal current collector and on the metal current collector; and a lithium manganese rich (LMR) positive electrode layer, the LMR positive electrode layer being compressed together with the metal current collector and on the coating, such that the coating is between the metal current collector and the lithium manganese rich positive electrode layer.

[0004] In one embodiment, the coating also includes ultra-high BET carbon and acetylene black. In another embodiment, the carbon nanotubes include a mixture of multi-walled carbon nanotubes and single-walled carbon nanotubes. In yet another embodiment, the metal current collector is a metal foil, such as aluminum. In yet another embodiment, the binder is acrylic acid or modified polyvinylidene fluoride (PVDF). In some embodiments, the thickness of the pre-coating layer can be controlled between 0.5 μm and 20 μm, and the average particle size can be controlled between 0.1 μm and 10 μm.

[0005] In other embodiments, the pre-coating layer is pressed only before being pressed together with the lithium-rich manganese positive electrode layer. In additional embodiments, the electrode assembly includes a pre-coating layer with polymer beads and BaTiO 3 Blended carbon nanotubes, including BaTiO 3 The particles constitute from 10% to 80% of the blend.

[0006] In another aspect, the present disclosure relates to a method for manufacturing an electrode assembly. The method includes: producing a pre-coating layer by applying a coating layer consisting of dispersed carbon, carbon nanotubes, ultra-high BET carbon, and a binder on a metal current collector; pressing the pre-coating layer onto the metal current collector; applying an LMR slurry also on the pre-coating layer; and pressing the LMR slurry onto the pre-coating layer so that the pre-coating layer is between the metal current collector and the lithium manganese-rich electrode layer.

[0007] In some embodiments, the LMR slurry further comprises acetylene black and ultra-high BET carbon. In other embodiments, the carbon nanotubes comprise a mixture of multi-walled carbon nanotubes and single-walled carbon nanotubes. In further embodiments, the binder used is acrylic acid, which may be modified PVDF. In yet further embodiments, the method further comprises mixing the polymer beads and BaTiO 3 Blended as a binder, in which BaTiO 3 The blend ratio of particles to polymer beads is between 10% and 80%.

[0008] In yet another aspect, the present disclosure is directed to a battery comprising a current collector, an electrolyte, a separator, and a pre-coating layer compressed directly onto a metal current collector foil. The pre-coating layer comprises a blend of dispersed carbon, both single-walled carbon nanotubes and multi-walled carbon nanotubes, ultra-high BET carbon, and a lithium-rich manganese carbon black electrode layer positioned directly on top of and in direct contact with the pre-coating layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 is a schematic cross-sectional view of an electrode assembly according to one embodiment.

[0010] Figure 2 is a schematic cross-sectional view of a pre-coating layer.

[0011] Figure 3 is a schematic cross-sectional view of an LMR layer according to one embodiment.

[0012] Figure 4 It is a flow chart of the electrode assembly process. DETAILED DESCRIPTION

[0013] Embodiments are described herein. However, it should be understood that the disclosed embodiments are merely examples and that other embodiments may take different and alternative forms. The drawings are not necessarily drawn to scale. Some features may be enlarged or minimized to show details of particular components. Therefore, the specific structural details and functional details disclosed herein should not be interpreted as limiting, but merely as a representative basis for teaching those skilled in the art.

[0014] The various features shown and described with reference to any one of the accompanying drawings may be combined with features shown in one or more other drawings to produce embodiments not explicitly shown or described. The combinations of features shown provide representative embodiments for typical applications. However, for specific applications or implementations, various combinations and modifications of features consistent with the teachings of the present disclosure may be desired.

[0015] Lithium-rich manganese electrodes (commonly referred to as LMR) may have increased internal resistance when in a low state of charge (SOC) region, which can affect cell performance and efficiency. The present disclosure introduces a layering method for incorporating conductive materials. Carbon and carbon nanotubes (CNTs), known for their conductive properties, are used to form a pre-coating on a current collector. The pre-coating combines both carbon black and ultra-high surface carbon with single-walled carbon nanotubes and multi-walled carbon nanotubes. The LMR slurry is deposited on top of the pre-coated current collector. The interfacial resistance of the electrode assembly can be increased by incorporating ultra-high surface area carbon and acetylene black (a type of carbon black) as characterized by the Brunauer, Emmette and Teller method (BET carbon). The interaction between the pre-coating and the cathode produces an interface with reduced surface charge transfer resistance.

[0016] The layered approach can result in a reduction in internal cell resistance, potentially increasing power capacity. The combination of conductive materials (such as acetylene black and ultra-high BET carbon) with CNTs creates two conductive layers. This layered approach reduces the resistance in the cathode electrode. In one embodiment, the LMR cathode can integrate a specific ratio of ultra-high BET carbon, acetylene black and other conductive materials to achieve increased resistance reduction. This combination can vary depending on the results and production methods. Another embodiment can incorporate a variation of the layered approach, in which the order, composition or density of the layers can be changed to achieve specific performance criteria.

[0017] Now referring to the accompanying drawings, Figure 1 A schematic cross-sectional view of an electrode assembly 10 according to one embodiment of the present disclosure is shown. The electrode assembly 10 has a current collector 12, a pre-coating layer 14, and a slurry layer 16. The current collector 12 serves as a base layer and may be a metal current collector, which may be aluminum. The pre-coating layer 14 is deposited onto the current collector 12 and may include carbon nanotubes 18, ultra-high surface carbon black 20, and a binder 22, which may be an acrylic acid, such as modified polyvinylidene fluoride (PVDF). The binder 22 may also include polymer beads and BaTiO 3 BaTiO in binder 22 3 The blending ratio of the particles is in the range of about 10% to about 80%. Ceramic material BaTiO combined with polymer beads 3 Produce carbon nanotubes with suitable dielectric properties. The average particle size of the pre-coat layer 14 can be controlled within 0.1 μm to 10 μm. The thickness of the pre-coat layer can be controlled between 0.5 μm and 20 μm. The slurry layer 16 applied to the pre-coat layer 14 can also include carbon nanotubes 18, ultra-high surface carbon black 20, a binder 22, acetylene black 24 and a cathode material 26. The cathode material 26 can be LMR particles that promote primary electrochemical reactions. The cathode material 26 characterizes the slurry layer as an LMR layer.

[0018] The carbon nanotubes 18 of the pre-coat layer 14 and the slurry layer 16 can include a mixture of single-walled carbon nanotubes (SWCNT) and multi-walled carbon nanotubes (MWCNT). The ratio of the mixture can be determined by the mechanical properties of the application, and MWCNT provides mechanical strength due to its multi-layer concentric cylindrical structure, while SWCNT has a higher conductivity. The different geometric shapes and sizes between SWCNT and MWCNT can make it better dispersed in the doping layer. The pre-coat layer 14 also contains ultra-high surface carbon black 20 (commonly referred to as "BET carbon"), which is a form of carbon black with a large surface area. The Brunauer, Emmette and Teller (BET) method (a technique for measuring the surface area of ​​porous materials) is used to quantitatively characterize the surface area of ​​this expansion. The surface characteristics of BET carbon are related to its adsorption capacity. Carbon that particularly shows surface characteristics characterized by BET will be referred to as ultra-high BET carbon.

[0019] Reference now Figure 2 , a schematic cross-sectional depiction of a precoat layer 28 is shown. The precoat layer 28 comprises carbon nanotubes 30, which may be a combination of SWCNTs and MWCNTs. The mixture of SWCNTs and MWCNTs is affected by the specific mechanical properties of the application. For example, MWCNTs with their multi-layer concentric cylindrical design provide mechanical strength, while SWCNTs are known for their higher electrical conductivity. Ultra-high surface carbon black 32 is also included in the composition of the precoat layer 28. This particular type of carbon black (commonly referred to as "BET carbon") has a huge surface area. The surface area is measured using the Brunauer, Emmette and Teller (BET) technique (a method for quantifying the surface area of ​​porous materials). The high surface area of ​​BET carbon is associated with a higher absorption capacity relative to low surface area carbon. In order to provide structural cohesion, the average particle size of the precoat layer 28 is preferably in the range of 0.1 μm to 10 μm, and the total thickness of the precoat layer 28 is preferably between 0.5 μm and 20 μm. In addition, the pre-coat layer 28 also includes a binder 34, which can be an acrylic, such as PVDF, which has been modified or slightly treated to better suit as a binder. The binder 34 can also be made of polymer beads and BaTiO 3 BaTiO 3 The percentage of particles (ceramic material with specific properties) can be between 10% and 80% of the blend.The composition of the carbon nanotubes can be modified to change their dielectric properties.

[0020] refer to Figure 3, which presents a cross-sectional depiction of a slurry layer 36. The slurry layer 36 is applied on top of the pre-coating layer to form an electrode assembly. Within the slurry layer 36, there are carbon nanotubes 38, which may be a mixture of both SWCNTs and MWCNTs. Depending on the specific mechanical properties of the application, the ratio of SWCNTs to MWCNTs may be varied. In addition to the carbon nanotubes, the slurry layer 36 also incorporates ultra-high surface carbon black 40 and acetylene black 42 to reduce interfacial resistance, wherein the ultra-high surface carbon black is characterized by its surface area measured by the BET technique. The presence of BET carbon in the slurry layer is to achieve its adsorption capacity. In addition, for the main electrochemical processes in the battery cell, the slurry layer 36 may contain other cathode materials 42, such as LMR particles. When cured to form a solid active layer, the slurry layer is also an LMR layer. The LMR layer 36 also contains a binder 44, which may be an acrylic acid, such as modified PVDF. The binder 44 may also be composed of polymer beads and BaTiO 3 The blend consists of BaTiO 3 The BaTiO in the blend constitutes 10% to 80%. 3 This specific ratio of changes the dielectric properties of the adhesive 44.

[0021] Reference now Figure 4 , a flow chart presents a sequential process in the preparation of an electrode assembly according to an embodiment of the present disclosure. The process starts from frame one 46, which represents a current collector, which is a basic component of subsequent steps. The precoat is then applied directly to the current collector. Advancing to frame two 48, the precoat undergoes a pressing process together with the current collector below. This compression increases the adhesion and uniformity of the precoat on the current collector, thereby preparing for the next stage. In frame three 50, a slurry layer is applied directly on top of the previously pressed precoat. The slurry layer encapsulates various components, including carbon nanotubes (both SWCNTs and MWCNTs), ultra-high BET carbon, acetylene black / carbon black and may include other cathode materials, such as lithium LMR particles. Frame four 52 represents the final formation step, in which the slurry layer, precoat and current collector are pressed together. The pressing process helps to form a cohesive electrode assembly.

[0022] The algorithm, method or process disclosed or suggested herein can be delivered to or implemented by a computer, controller or processing device, which may include any dedicated electronic control unit or programmable electronic control unit. Similarly, the algorithm, method or process can be stored in various forms as data and instructions that can be executed by a computer or controller, including but not limited to information permanently stored on a non-writable storage medium such as a read-only memory device and information that can be changed and stored on a writable storage medium such as an optical disk, a random access memory device or other magnetic and optical media. The algorithm, method or process can also be implemented by a software executable object. Alternatively, suitable hardware components can be used, such as a combination of an application-specific integrated circuit, a field programmable gate array, a state machine or other hardware components or devices, or firmware, hardware and software components to implement the algorithm, method or process in whole or in part.

[0023] Although exemplary embodiments are described above, these embodiments are not intended to describe all possible forms covered by the claims. The words used in the specification are words of description rather than limitation, and it should be understood that various changes can be made without departing from the spirit and scope of these disclosed materials.

[0024] As previously described, features of the various embodiments may be combined to form additional embodiments of the present disclosure that may not be explicitly described or illustrated. Although various embodiments may have been described as providing advantages or being preferred over other embodiments or prior art implementations with respect to one or more desired characteristics, it will be recognized by those of ordinary skill in the art that one or more features or characteristics may be compromised to achieve desired overall system properties, depending on the specific application and implementation. These properties may include, but are not limited to, strength, durability, marketability, appearance, packaging, size, serviceability, weight, manufacturability, ease of assembly, etc. Therefore, embodiments that are described as being less desirable than other embodiments or prior art implementations with respect to one or more characteristics are within the scope of the present disclosure and may be desirable for a particular application.

[0025] According to the present invention, an electrode assembly is provided, which has: a metal current collector; a coating composed of dispersed carbon, carbon nanotubes and a binder, the coating being compressed together with the metal current collector and on the metal current collector; and a lithium manganese rich (LMR) positive electrode layer, the LMR positive electrode layer being compressed together with the metal current collector and on the coating, so that the coating is between the metal current collector and the lithium manganese rich positive electrode layer.

[0026] According to one embodiment, the coating further comprises ultra-high BET carbon.

[0027] According to one embodiment, the coating further comprises acetylene black.

[0028] According to one embodiment, the carbon nanotubes include a mixture of multi-walled carbon nanotubes and single-walled carbon nanotubes.

[0029] According to one embodiment, the metal current collector is a metal foil.

[0030] According to one embodiment, the metal foil is aluminum.

[0031] According to one embodiment, the adhesive comprises acrylic.

[0032] According to one embodiment, the acrylic acid is modified polyvinylidene fluoride.

[0033] According to one embodiment, the average particle size of the coating is between 0.1 μm and 10 μm.

[0034] According to one embodiment, the thickness of the coating is between 0.5 μm and 20 μm.

[0035] According to one embodiment, the LMR positive electrode layer further comprises acetylene black.

[0036] According to one embodiment, the binder further comprises polymer beads and BaTiO 3 of blends.

[0037] According to one embodiment, BaTiO 3 The blending ratio of the particles to the polymer beads ranges from 10% to 80%.

[0038] According to the present invention, a method includes: pressing a coating of dispersed carbon, carbon nanotubes, ultra-high BET carbon and a binder on a metal current collector; applying a lithium manganese rich (LMR) slurry of acetylene black and carbon nanotubes on top; and pressing the LMR slurry onto the coating so that the coating is between the metal current collector and the LMR slurry.

[0039] In one aspect of the present invention, the LMR-rich slurry further includes ultra-high BET carbon.

[0040] In one aspect of the present invention, the carbon nanotubes include a mixture of multi-walled carbon nanotubes and single-walled carbon nanotubes.

[0041] In one aspect of the invention, the binder comprises acrylic.

[0042] In one aspect of the invention, the acrylic acid is modified polyvinylidene fluoride.

[0043] In one aspect of the present invention, the binder further comprises polymer beads and BaTiO 3 Blending.

[0044] According to the present invention, a battery is provided, which has: an electrolyte; a separator; and an electrode, wherein the electrode has a lithium manganese-rich acetylene black and carbon nanotube layer, and the lithium manganese-rich acetylene black and carbon nanotube layer is directly compressed on top of a pre-coating layer composed of dispersed carbon, carbon nanotubes and ultra-high BET carbon on a collector foil and is in direct contact with the pre-coating layer.

Claims

1. An electrode assembly, comprising: Metal current collector; a coating composed of dispersed carbon, carbon nanotubes, and a binder, the coating being compressed with and on the metal current collector; as well as A lithium manganese rich (LMR) positive electrode layer is compressed together with the metal current collector and on the coating layer such that the coating layer is between the metal current collector and the lithium manganese rich positive electrode layer.

2. The electrode assembly of claim 1, wherein the coating further comprises ultra-high BET carbon.

3. The electrode assembly of claim 1, wherein the coating further comprises acetylene black.

4. The electrode assembly of claim 1, wherein the carbon nanotubes comprise a mixture of multi-walled carbon nanotubes and single-walled carbon nanotubes.

5. The electrode assembly of claim 1, wherein the metal current collector is an aluminum metal foil.

6. The electrode assembly of claim 1, wherein the binder comprises modified polyvinylidene fluoride acrylic acid.

7. The electrode assembly of claim 1, wherein the LMR positive electrode layer further comprises acetylene black.

8. The electrode assembly of claim 1, wherein the binder further comprises a blend of polymer beads and BaTiO3 in the coating.

9. A method comprising: Pressing a coating consisting of dispersed carbon, carbon nanotubes, ultra-high BET carbon and a binder onto a metal current collector; A lithium manganese rich (LMR) slurry of acetylene black and carbon nanotubes is applied on top; as well as The LMR slurry is pressed onto the coating so that the coating is between the metal current collector and the LMR slurry.

10. The method of claim 9, wherein the LMR-rich slurry further comprises ultra-high BET carbon.

11. The method of claim 9, wherein the carbon nanotubes comprise a mixture of multi-walled carbon nanotubes and single-walled carbon nanotubes.

12. The method of claim 9, wherein the adhesive comprises acrylic.

13. The method of claim 9, wherein the acrylic acid is modified polyvinylidene fluoride.

14. The method of claim 9, wherein the binder further comprises blending polymer beads and BaTiO3.

15. A battery comprising: Electrolytes; separators; as well as An electrode having a lithium manganese rich acetylene black and carbon nanotube layer compressed directly on top of and in direct contact with a pre-coating layer of dispersed carbon, carbon nanotubes and ultra-high BET carbon on a current collector foil.